Urgency of the Death Penalty in Efforts to Create a Deterrent Effect in Eradicating the Crime of Narcotics Trafficking - Joko, Tri; Ngazis, Muhammad (Jurnal Hukum Khaira Ummah, 2025)
Abstract. The type of research in this thesis is empirical research. Empirical law research is also called sociological law research, which is a legal research that studies law conceptualized as actual behavior, as an unwritten social phenomenon, experienced by everyone in social life. Based on the research results, it can be seen thatThe regulation of the death penalty for narcotics traffickers in Indonesia is currently regulated in Article 114 and Article 119 of the Republic of Indonesia Law Number 35 of 2009 concerning Narcotics, however, the existence of PK and pardons are often the reasons for postponing or even canceling the execution of the death penalty for narcotics dealers. The obstacles that result in the failure to realize the deterrent effect through the death penalty in eradicating narcotics crimes today are the formal legal weaknesses, namely the existence of PK and gerasi which can cancel and postpone the execution of the death penalty for narcotics dealers. The material legal weaknesses are in the form ofLaw Number 11 of 2008 in conjunction with Law Number 19 of 2016 concerning Electronic Information and Transactions andRepublic of Indonesia Law Number 35 of 2009 Concerning Narcoticsdoes not specifically contain regulations related to the distribution of narcotics electronically or through social media and the internet. This can be a source of increasing digital-based narcotics circulation that is difficult to prosecute. These various circumstances will clearly result in the absence of a deterrent effect for perpetrators of narcotics distribution.Empirical constraints in the form of economic needs that can be due to dealers being drug addicts so they need narcotics through efforts to become dealers, or purely dealers are only looking for profit for their economic needs, have resulted in dealers having no choice not to commit the crime of drug trafficking. The solution that can be done is to regulate the exception of granting pardons to drug dealers in the Republic of Indonesia Law Number 5 of 2010 concerning Amendments to Law Number 22 of 2002 concerning Pardons considering that drug trafficking is a serious problem that can damage the future of the nation and state. Specifically regulate the digital distribution of narcotics, so that drug dealers in the digital world can be subject to the death penalty as the maximum penalty with aggravation. The government needs to supervise the community, especially teenagers seriously, especially for people with weak economies regarding the existence of drug trafficking.